2012
DOI: 10.1179/1743132811y.0000000026
|View full text |Cite
|
Sign up to set email alerts
|

Protective effects of erythropoietin in experimental spinal cord injury by reducing the C/EBP-homologous protein expression

Abstract: Endoplasmic reticulum (ER) stress was triggered at the early stage of SCI. Increased expression of CHOP can be found in the injured segment of the spinal cord after injury. EPO treatment could prevent pathological alterations from severe spinal cord injury by reducing expression of CHOP.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 24 publications
0
13
0
Order By: Relevance
“…Recent studies indicate that ER stress is an early tissue reaction after SCI in different models, including mechanical trauma and hypoxia. 8, 10, 11, 12, 13, 27 Here we show a fast activation of a range of UPR responses after SCI, including the expression of the proximal components ATF4 and XBP1, major transcription factors governing this pathway, in addition to the upregulation of downstream target genes. Remarkably, UPR activation was also observed in regions distant from the primary injury zone, suggesting the activation of a broad ER stress response in the spinal cord after damage.…”
Section: Discussionmentioning
confidence: 65%
“…Recent studies indicate that ER stress is an early tissue reaction after SCI in different models, including mechanical trauma and hypoxia. 8, 10, 11, 12, 13, 27 Here we show a fast activation of a range of UPR responses after SCI, including the expression of the proximal components ATF4 and XBP1, major transcription factors governing this pathway, in addition to the upregulation of downstream target genes. Remarkably, UPR activation was also observed in regions distant from the primary injury zone, suggesting the activation of a broad ER stress response in the spinal cord after damage.…”
Section: Discussionmentioning
confidence: 65%
“…24 In addition, modulation of ER stress molecules BiP, CHOP, XBP-1, and ATF4 decreased motoneuron death 17 and improved functional recovery after SCI. [25][26][27][28] Our own work with axotomized RGCs has shown that manipulating CHOP and XBP-1 in opposite directions, by deleting CHOP or by overexpressing XBP-1s, exerts striking RGC-protective effects. 16 Because XBP-1 regulates numerous genes that are involved in multiple cellular functions, it is important to define the downstream mechanism by which XBP-1 contributes to neuroprotection.…”
Section: Therapeutic Strategies Targeting Er Stress For Neuroprotectionmentioning
confidence: 99%
“…ER stress markers also have been detected in cortex after stroke 21, 22 and in motoneurons in a mouse model of ALS 23 . Moreover, modulation of ER stress protected cortical neurons in models of ischemia and TBI 24 , decreased spinal motoneuron death 17, 23 and improved functional recovery after SCI 25-28 . ER stress has been reviewed extensively in relation to chronic neurodegenerative diseases 29-33 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent studies indicate that ER stress is an early tissue reaction after SCI in different models, including mechanical trauma and hypoxia. 8,[10][11][12][13]27 Here we show a fast activation of a range of UPR responses after SCI, including the expression of the proximal components ATF4 and XBP1, major transcription factors governing this pathway, in addition to the upregulation of downstream target genes. Remarkably, UPR activation was also observed in regions distant from the primary injury zone, suggesting the activation of a broad ER stress response in the spinal cord after damage.…”
Section: Discussionmentioning
confidence: 99%